Electrochemical studies toward proteomic analysis - Alvarez de Eulate Diaz de San Martin, Eva Maria (Curtin University, 2014)
This thesis provides the basis for a label-free bioanalytical platform using electrochemical analysis at liquid –liquid interfaces. The possibility to detect biomolecules such as proteins in a label-free manner via adsorption and ion-transfer was achieved. Several pre-treatment steps used in proteome analysis, such as protein pre-concentration and digestion, were studied. The results demonstrate the promise of this strategy for the detection and identification of proteins.